1995
DOI: 10.1037/0033-3204.32.4.592
|View full text |Cite
|
Sign up to set email alerts
|

Tough guys: Psychotherapeutic strategies with law enforcement and emergency services personnel.

Abstract: The men and women who work in law enforcement and emergency services-the "tough jobs"-are exposed to special kinds of traumatic events and daily pressures that sometimes overwhelm defenses and result in maladaptive psychological syndromes. By dint of attitude, training, and social norms, these "tough guys" are often resistant to psychotherapy in its traditional forms, and so special therapeutic approaches are required. This article describes the types of stresses and problems experienced by police officers, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 27 publications
2
65
0
Order By: Relevance
“…The use of open discussion at the fire station was also found to include humour that may be considered by the firefighters to be inappropriate in other locations and is consistent with other firefighter research that has found humour to be present on fire stations (Miller, ). This humour will often include details or information about the incident that has recently been attended and is considered to result in an increased bond or a sense of closeness between the firefighters (Fullerton, McCarroll, Ursano, & Wright, ), as well as potentially desensitizing the firefighter from the trauma that had recently been witnessed (Miller, ). Other studies, such as the meta‐analytic review of front‐line emergency workers by Prati and Pietrantoni () examined the role of both received and perceived social support and describe social support as being both positive and negative.…”
Section: Discussionsupporting
confidence: 82%
“…The use of open discussion at the fire station was also found to include humour that may be considered by the firefighters to be inappropriate in other locations and is consistent with other firefighter research that has found humour to be present on fire stations (Miller, ). This humour will often include details or information about the incident that has recently been attended and is considered to result in an increased bond or a sense of closeness between the firefighters (Fullerton, McCarroll, Ursano, & Wright, ), as well as potentially desensitizing the firefighter from the trauma that had recently been witnessed (Miller, ). Other studies, such as the meta‐analytic review of front‐line emergency workers by Prati and Pietrantoni () examined the role of both received and perceived social support and describe social support as being both positive and negative.…”
Section: Discussionsupporting
confidence: 82%
“…Fear, horror, and helplessness, the feelings that characterize traumatic incidents in the community (DSM-IV;American Psychiatric Association, 1994), are not the most threatening feelings for ambulance personnel. In fact, many of them pride themselves on their emotional toughness (Miller, 1995) and are disappointed when the career does not present enough of these challenging experiences. Instead, the types of incidents that emerged as critical in this study are ones that evoke feelings of inability to help often co-existent with overwhelming compassion.…”
Section: Discussionmentioning
confidence: 98%
“…However, secondary trauma and vicarious trauma can produce PTSD symptoms that are markedly similar to those elicited by primary trauma (Figley 1995). Although EMDs are not directly exposed to physical danger, this population are confronted with PTEs through assisting civilians in highly stressful situations, and exposure to the traumatic events experienced by others is inherent in the role (Miller 1995). These PTEs are experienced vicariously rather than directly (Miller 1995), thus the current study will assess PTSD in relation to vicarious trauma.…”
Section: Negative Post-trauma Outcomesmentioning
confidence: 93%